P Pengaruh Budaya Terhadap Penggunaan TOGA (Tanaman Obat Keluarga) Di Masyarakat Desa Terombongsari: Pengaruh Budaya Terhadap Penggunaan TOGA (Tanaman Obat Keluarga) Di Masyarakat Desa Terombongsari - Diah Vinalisa Hasna Shofia; Iwan Yuwindry; Faisal Rahman (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: Terombongsari Village community is very much using TOGA (Family Medicinal Plants) as therapy independently. The people there tend to prefer TOGA over synthetic treatment, apart from minimal side effects, TOGA is also easy to get in people's homes. The community decides to do self-medication is influenced by several factors, one of which is culture. Culture is defined as a hereditary habit that occurs in the Terombongsari village community. Objective: This study aims to analyze the influence of culture on the use of TOGA in the Terombongsari Village community. Methods: This research uses analytical observational research with cross sectional research design. The sample is adults aged at least 17 years, totaling 92 families who routinely use TOGA. Sample selection by purposive sampling method. Collecting data with a questionnaire sheet, the data were analyzed using the Kendall tau-b test with a 95% confidence level. Results: The results show that 79.3% of the culture of using TOGA in the Terombongsari Village community is positive. The results in the use of TOGA are in the good category as much as 90.2%. The results of the bivariate analysis obtained a p-value of 0.0001, which means Ha is accepted. Conclusion: There is a cultural influence on the use of TOGA in the community of Terombongsari Village.